GE_GERICHTE C/1223/2013 vom 11. April 2014 - GE Cour de justice (2014)
MODIFICATION(EN GÉNÉRAL); DIVORCE; NULLITÉ; MODIFICATION DES CIRCONSTANCES; MINIMUM VITAL; NOVA | CO.19.2; CO.20.1; CC.27.2; CC.134.2; CC.286.2